Willingness to Pay for Eco‐Certified Refurbished Products: The Effects of Environmental Attitudes and Knowledge. (17th June 2015) - Harms, Rainer; Linton, Jonathan D.
Summary: Refurbishing products, which are increasingly sold in business‐to‐consumer markets, is a key strategy to reduce waste. Nevertheless, research finds that consumers' willingness to pay (WTP) for refurbished products is low. Strategies for a higher WTP are needed in order to grow consumer markets for refurbished products. Eco‐certification of refurbished products may be a key strategy here. Drawing on the consumer WTP literature concerning "green" products, we investigate the impact of independent eco‐certificates. Our analysis is based on a survey of 231 potential customers. The results suggest that, across various product categories, the WTP for products with refurbished components is significantly lower. Adding an eco‐certificate tends to return the WTP toward the virgin product level. We show that consumers with proenvironmental attitudes particularly exhibit green buying behavior. Our findings indicate that eco‐certification is often worthwhile because it enhances the business rationale for producing products with refurbished components.